2020
DOI: 10.1088/1361-6595/ab61e3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helium/propane–butane atmosphere on the synthesis of graphene in plasma jet system

Abstract: An experimental and theoretical study was performed on helium/propane-butane plasma, which enabled assembly of advanced carbon nanostructures, such as multilayer graphene flakes. A plasma jet was created at pressures ranging from 350 to 710 Torr, and with direct current plasma torch powers from 28 to 35 kW at varying mass ratios of helium to propane-butane 1:7.5 to 1:5. Graphene production was confirmed by different analytical techniques. The non-catalytic synthesis in the plasma jet volume provided the graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…From the perspective of the precursor, atmospheric pressure MW plasma decomposition of ethanol (in the aerosol form [ 6 ] or vapourised [ 7,8 ] ) is a well‐established method for the synthesis of good‐quality GNS. In comparison to ethanol and its isomer dimethyl ether (DME), [ 9 ] attempts involving other organic sources (methanol, isopropyl alcohol, [ 9 ] methane, [ 10,11 ] acetylene, [ 12 ] propane–butane, [ 13,14 ] etc.) were not as satisfactory and often resulted in the synthesis of highly disordered structures, suggesting an insufficient understanding of underlying physical and chemical processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of the precursor, atmospheric pressure MW plasma decomposition of ethanol (in the aerosol form [ 6 ] or vapourised [ 7,8 ] ) is a well‐established method for the synthesis of good‐quality GNS. In comparison to ethanol and its isomer dimethyl ether (DME), [ 9 ] attempts involving other organic sources (methanol, isopropyl alcohol, [ 9 ] methane, [ 10,11 ] acetylene, [ 12 ] propane–butane, [ 13,14 ] etc.) were not as satisfactory and often resulted in the synthesis of highly disordered structures, suggesting an insufficient understanding of underlying physical and chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were further used in the studies of physical and chemical processes, including chemical kinetics, of decomposition of precursors and consequent nucleation and growth of GNS. Besides the abovementioned model developed by Tsyganov [ 17 ] describing the synthesis in MW surface wave discharge, Shavelkina et al [ 14 ] developed a numerical model of propane–butane/helium plasma jet and showed that C 2 H provided additional C 2 production, leading to the formation of supersaturated vapour from C 2 molecules at temperatures of 2500–3500 K. Nucleation conditions and growth of GNS from Ar/CH 4 gas mixture were described by Meunier et al [ 25 ] in an inductively coupled plasma reactor at reduced pressure (55 kPa), including a study of carbon gas expansion. Their model showed that by varying the plasma expansion angle and methane flow rate, it should be possible to control the thickness and size of GNS.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of graphene synthesised in the volume of a plasma flow are determined by its composition and, as shown by modelling the chemical kinetics of the conversion process of a propane–butane mixture in helium plasma, C 2 and C 2 H radicals participate in the nucleation and growth of graphene. 8 Thus, hydrogen has to be present in the graphene structure during the synthesis. The H concentration can be controlled by varying the synthesise parameters and cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, this synthesis process is realized only at a high-enough temperature environment, above 4500 K, and some of the gas-products stay in the form of simple hydrocarbons (CH4, C2H2, C2H4 etc.) [3,4]. Depending on the plasma source and stability of the environment [5], the precursor can be partially decomposed by a so-called low temperature channel, where higher hydrocarbons and aromatic compounds containing large amounts of hydrogen are produced [6].…”
Section: Introductionmentioning
confidence: 99%